The effect of micro climate factors on energy consumption optimization approach in Tehran urban buildings - pariz Amiri Ade; Saeed Tizghalam zenozi; Mehrdad Javidi Nejad (تحقیقات کاربردی علوم جغرافیایی, 2022)
this study is designed to investigate the impact of micro climatic factors on optimizing energy consumption in Tehran urban buildings. The present study is of applied purpose and analytical method. Libraries and documents were used to collect the required data. Design Builder software was used to achieve the purpose of the research. The information given to the software is the thickness of the walls: exterior 20 cm - internal 15 cm, south windows (double shell balcony with 40% glass), northern windows 30%, brick exterior walls with natural ventilation were used. The results of this study showed that the orientation of the building on the site due to Tehran climate and the results obtained from Ecotect software was rotated about 25 degrees to the southwest to prevent direct sunlight from the east and west. And reduce the heat loads on the building. The volume of the building was designed in a stepped fashion, and while it could aesthetically enhance its strength, it could reduce the wind load on the upper floors. Green roofs were also designed on the exposed roofs, and according to the results of the analysis, the green roof can be very effective in reducing heating and cooling loads. The eastern and western fronts were also considered to be non-popping because of the results obtained in Design Builder software for daylight, which may result in dazzling workspaces such as kitchens sometimes day in the year.